Implementasi PM 83 Tahun 2017 Dalam Penanganan Gangguan Burung Dan Hewan Liar di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Shauza Amelia W.P; Djoko Widagdo (Journal of Creative Student Research, 2024)
Apron Movement Control (AMC) is a unit that works directly on the air side and ensures flight safety. Maintaining security and safety can be done by ensuring the aircraft is in good condition, maintaining the condition of the airside area to avoid Foreign Object Debris (FOD), the aircraft crew is in good condition and has a license in accordance with established standards. Problems that often disrupt flight safety can come from anywhere, such as disturbances from birds and other animals. The aim of this research is to find out how PM 83 of 2017 is implemented in dealing with bird and wild animal disturbances at airports. This research uses qualitative methods and the types of data used are primary data and secondary data. The data collection techniques used in this research are observation, interviews and documentation. By using analytical techniques in the form of data reduction, data presentation and conclusions. Testing the validity of the data used in this research is technical triangulation and source triangulation. The results of this study indicate that the Implementation of PM 83 of 2017 at General Ahmad Yani International Airport, Semarang, carried out by Apron Movement Control (AMC) officers went well, namely by carrying out land maintenance and routine inspections, and the obstacles faced were the birds' habituation to the sound of the bird repellent, so the current solution for officers is to replace the sound variations produced by the device. If the sound changes are carried out periodically, the effectiveness is expected to be higher.